Lots of Lancelets or Not? Diversity of Cephalochordates in the Tropical Eastern Pacific - Maycol Ezequiel Madrid Concepcion; Kenneth S. Macdonald; Amy C. Driskell; Regina Wetzer; Maikon Di Domenico; Rachel Collin (Diversity)
As close relatives of the vertebrates, cephalochordates have been the focus of significant evo–devo and genomic research; however, their biodiversity and systematics remain poorly known. In particular, few species have been documented in the eastern Pacific and there are few published observations for this region. Using sequences from COI and 16S DNA barcode markers and morphological observations from 16 animals collected incidentally during other studies, we document the presence of three species of amphioxus on the Pacific coast and one from the Caribbean coast of Panama. The high genetic diversity recovered from so few samples suggests that the application of molecular taxonomy to neotropical amphioxus would likely uncover additional species and could help to more easily delineate morphological differences among taxa.